The Effect of Aerobic Exercise on Blood Glucose Level among Patients with Type-2 Diabetes Mellitus - Yasmiin Khoirul Bariyyah; Endang Sawitri; Rahmat Bakhtiar (Universitas Muhammadiyah Kalimantan Timur, 2021)
Abstract: Diabetes Mellitus is the disease which causes premature mortality, and the leading cause of blindness, heart disease, and kidney failure in the world with increasing prevalance. Exercise is fundamental in Diabetes Mellitus management which functions to improve insulin sensitivity and control blood glucose level. A number of studies have been carried out to explore the effect of aerobic exercises on blood glucose level among patients with type-2 Diabetes Mellitus. The research aimed to evaluate the effect of aerobic exercise’s type, frequency, intensity and duration on blood glucose level among patients with type-2 Diabetes Mellitus. This study was systematic review. The literature searches were specified from 2005-2020 through Pubmed and Google Scholar. 40 studies in total based on specific criteria was included to this study. Thirty-nine out of forty studies revealed that a variety of aerobic exercises such as walking, gymnastic (diabetic, aerobic, foot, ergonomic), step test as well as static cycling give impact on lowering blood glucose level. Seventeen out of forty studies fulfilling the criteria of frequency, duration and intensity showed that exercise helps reduce blood glucose level. In conclusion, performing aerobic exercise regularly and appropriately helps to lower blood glucose level among patients with type-2 Diabetes Mellitus.